Reconciling pressures for integration and autonomy within multinational corporations: an examination of personnel policies and practices. (1st January 2011) - Ryan, Jason; Gibbons, Patrick
This paper examines and contrasts the human resource policies and practices of US multinational enterprises (MNEs) towards their overseas subsidiaries, taking Japan and Ireland as examples. It demonstrates how economic, social, cultural and other environmental factors mediate the relationship between parent and subsidiary. The analysis draws upon institutional theory and its key concept, isomorphism, to explain the interactions of parents and subsidiaries in different environments. The focus is on three specific HR areas: (a) training, (b) performance assessment and (c) recruitment. The paper examines the countervailing pressures towards corporate integration or local responsiveness encountered in these areas. An examination of these pressures provides valuable insights into the implementation of HR policies and, in doing so, illuminates the environmental constraints under which the MNE operates in different settings. Three sets of issues relating to HR policies and practices are specified and recommended for future research.